Loraine Minish-Cooper Garden of Hope ... - Campbell, Sandy (University of Alberta Library, 2015)
The Garden of Hope is near the shore of Frame Lake. This rock stands near the entrance. A sign near the entrance reads: \"GARDEN OF HOPE Loranie Frances Minish-Cooper (1951 - 2002)\". \"Loraine believed in the power of hope and it was her wish that this garden would be a place of hope, peace and comfort for all. Established in 2003, this garden was lovingly designed, constructed, planted and maintained by family and friends, with generous support from many local businesses, the City of Yellowknife and the Yellowknife Community Foundation.\" ...